The Relationship of Workload and Shift Systems with Operator Fatigue Levels at PT XYZ - M. Khafid Ramadhon; Ariel Dwi Putra; Rizky Febriansyah; Rossy Ruwandra; Yudi Prastyo (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2026)
Work fatigue is a common problem in the manufacturing industry, especially in jobs with high physical activity and shift work systems. This study aims to determine the relationship between workload and work shifts on the level of operator fatigue at PT XYZ, a casting component manufacturing company that operates 24 hours with three shift systems. The study used an analytical observational method with a cross-sectional approach to 30 operators selected through total sampling techniques in the period October–November 2025. Data was obtained through questionnaires and analyzed using Spearman Rank and Chi-Square tests. The results show that most operators have workloads and fatigue levels in the medium to severe category. Statistical analysis showed a significant relationship between workload and fatigue level (p = 0.001; r = 0.610) as well as a significant relationship between work shifts and fatigue level (p = 0.018). Thus, it can be concluded that workload and shift work systems affect the level of operator fatigue so that better work management and shift management are needed to reduce the risk of work fatigue.